Study the Molar Ratio of the Reaction between Thalassemia s Drug (Deferoxamine) with Iron Over loud - Abdullah, Amer Hasan (Al-Nahrain Journal of Science, 2018)
Iron-Deferoxamine complex have been synthesized in vitro by the reaction of deferoxamine (which are use as therapeutic agent for removing iron overload from the bodies of thalassemia patients) with Fe(II) salt in aqueous medium. The geometry of the prepared complex as well as the mode of bonding were determined through FTIR, UV-Vis, mass spectral studies, metal content, and molar conductance. These studies revealed octahedral geometry for the complex with the general formula [FeII (DEF)]Cl2. Complex formation via molar ratio method and variation continuous method in aqueous solution have been also investigated and results were consistent to those found in the solid complexes with a ratio of (M:L) as (1 : 1). Conditional formation constant could also be calculated for [FeII (DEF)]Cl2 as 2.0 × 103. The effect of time on the formation of Iron – Deferoxamine complex has been also studied. This study showed that each 1×10-3M of deferoxamine needs 2.5 – 3 hrs to remove 1×10-3M of Iron (II) by formation coordination complex.